Gotska katedrala: uporaba kognitivne teorije v družboslovju pri pojasnjevanju nekaterih estetskih družbenih fenomenov - Krpič, Tomaž (Časopis za kritiko znanosti, 1999)
The basic thesis proposed by the author derives from his conviction that, in the study of cultural phenomena, we should focus not only on the form in which a work of art as representative of a specific culture appears or only on the mental strategies employed by individuals in their attempt to understand a work of art in a certain cultural context. Rather, to truly understand a certain cultural phenomenon, the study of cognitive (sensorial) processes in an individual's body must be taken into account. In order to justify this methodological shift in the study of cultural phenomena, the author attempts an interpretation of the phenomenon of late medieval Gothic art. He proposes that on entering a Gothic cathedral, an individual from the Middle Ages explained his or her sensorial experience as an experience of the Divine. The reason for this is the combined action of three negative artistic means of expression of the Divine and sensorial impulses intensified by the light pouring through colourful stained-glass windows.
Keywords: gotska umetnost; Middle Ages; srednji vek; katedrale; percepcija; kognitivna sociologija